Locating recurring themes in musical sequences - Doraisamy, Shyamala (Faculty of Computer Science and Information Technology, 1995)
Computer are now being used in almost all (sub) disciplines of music. Automated composition, music theory expert systems, architectural acoustics are just of these many areas.